Folk Music as an Important Tool in the Moral and Aesthetic Education of Students - Nazarova Diyora Jamolovna (Research Parks Publishing LLC, 2021)
By its very nature, music vividly depicts people's lives, their attitudes toward reality, and various inner experiences through a variety of sound colors. Music enhances people's spiritual and moral world by influencing their emotions. The article highlights the important role of folk music in the moral and aesthetic education of students.